2014
DOI: 10.1007/s10729-014-9291-1
|View full text |Cite
|
Sign up to set email alerts
|

Patient flow improvement for an ophthalmic specialist outpatient clinic with aid of discrete event simulation and design of experiment

Abstract: Continuous improvement in process efficiency for specialist outpatient clinic (SOC) systems is increasingly being demanded due to the growth of the patient population in Singapore. In this paper, we propose a discrete event simulation (DES) model to represent the patient and information flow in an ophthalmic SOC system in the Singapore National Eye Centre (SNEC). Different improvement strategies to reduce the turnaround time for patients in the SOC were proposed and evaluated with the aid of the DES model and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 17 publications
1
34
0
1
Order By: Relevance
“…The results of Amina et al (33) showed that the highest average time was related to the waiting time between requesting laboratory tests and receiving their results. The results of Pan et al (18) showed that the highest and lowest average time were, respectively, related to the patients' examinations by the residents studying in the 1st and 2nd years, and the time spent in the cashier station. Moreover, the results of Ameh et al (34) showed that the highest and lowest average of waiting time were related to the orthopedic clinic and dermatology clinic, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of Amina et al (33) showed that the highest average time was related to the waiting time between requesting laboratory tests and receiving their results. The results of Pan et al (18) showed that the highest and lowest average time were, respectively, related to the patients' examinations by the residents studying in the 1st and 2nd years, and the time spent in the cashier station. Moreover, the results of Ameh et al (34) showed that the highest and lowest average of waiting time were related to the orthopedic clinic and dermatology clinic, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Simulation allows examining the effects of different solutions to improve the current situation and reduces the costs and risks of actual implementation of solutions (17,18). The simulation with various scenarios can predict the results of making changes in the important elements of a system, including costs, waiting time, and staff, and help managers to make the right decisions to optimize the system performance (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…The model output results were compared to the actual operational data for fi scal year 2013 from the Geisinger Health System's electronic health records. Pan et al (2015) proposed the use of DES to represent patients and information fl ow in an ophthalmic specialist outpatient clinic. The model was used to identify strategies to improve patient experience by evaluating the total time between the arrival of a patient and the departure from the clinic (turnaround time).…”
Section: Related Workmentioning
confidence: 99%
“…Service quality of outpatient clinics are affected by numerous factors [4] [5], one of which is the design of the outpatient appointment system [6] [7]. Usually, a patient will make an appointment to obtain the scheduled time for his/her clinical visit before the outpatient service, and then he/she will visit the clinic according to this message [8].…”
Section: Introductionmentioning
confidence: 99%